T163. STRUCTURAL AND CONNECTIVITY CHANGES IN THE CEREBELLUM CONTRIBUTE TO EXPERIENCING AUDITORY VERBAL HALLUCINATIONS. (18th May 2020) - Pinheiro, Ana; Bouix, Sylvain; Makris, Nikos; Schwartze, Michael; Shenton, Martha; Kotz, Sonja
Abstract: Background: Auditory verbal hallucinations (AVH) have been explained in the context of the forward model, giving the cerebellum a prominent role. However, research utilizing multiple neuroimaging modalities has rendered results on the specificity of cerebellar contribution to AVH unclear. Methods: To examine the reliability and regional specificity of cerebellar changes in AVH, a systematic search of electronic databases through October 2019 was conducted to identify neuroimaging studies of the cerebellum in psychotic patients or nonclinical participants reporting AVH, focusing on structural MRI, diffusion tensor imaging, and resting state functional connectivity studies. Twenty-two studies were selected, including 892 participants with AVH (792 psychotic patients; 100 at-risk subjects) and 775 healthy controls. Activation likelihood estimate analysis (ALE) examined the reported coordinates for reduced volume, fractional anisotropy (FA) or connectivity (control participants > participants with AVH) and increased volume, FA or connectivity (participants with AVH > control participants). The consistency of cerebellar changes and their relationship with sociodemographic and clinical measures were meta-analyzed. Results: The ALE meta-analysis revealed changes in both anterior and posterior cerebellar lobes, with opposite patterns: whereas decreased volume or connectivity was identified in the right anterior cerebellum (lobule IV/V), increased volume or connectivity was identified in the bilateral posterior cerebellum (Crus I and II). A random-effects model with small sample corrections identified consistent changes in both volume and functional connectivity of the cerebellum in participants with AVH (g = .84; SE = .24, 95% CI [.33, 1.34]), which were enhanced in Crus I (g = 1.52, SE = .28, p = .006, 95% CI [.73, 2.31]) but not moderated by age, sex, medication, or illness duration. Discussion: The ALE meta-analysis confirms cerebellar structural and connectivity changes in psychotic and nonclinical participants reporting AVH. These changes may contribute to AVH due to altered sensory feedback and consequently to erratic prediction as described by the forward model. The current findings also indicate that not all cerebellar regions are equally affected by AVH: the most pronounced changes were observed in Crus I. Specifically, altered communication between Crus I and neocortical network nodes, including the prefrontal cortex, may contribute to ineffective cognitive control in AVH, leading to external misattributions of auditory feedback and a reduced sense of control over events in the environment.